Maintenance of physical activity and sedentary behavior change, and physical activity and sedentary behavior change after an abridged intervention: Secondary outcomes from the ACTIVATE Trial. Issue 16 (23rd April 2019) - Lynch, Brigid M.; Nguyen, Nga H.; Moore, Melissa M.; Reeves, Marina M.; Rosenberg, Dori E.; Boyle, Terry; Milton, Shakira; Friedenreich, Christine M.; Vallance, Jeff K.; English, Dallas R.
Abstract : Background: This brief report examines the maintenance of moderate to vigorous physical activity (MVPA) and sedentary behavior changes approximately 12 weeks after the delivery of the ACTIVATE Trial primary intervention (use of the Garmin Vivofit 2 activity tracker coupled with a behavioral feedback and goal‐setting session and 5 telephone‐delivered health coaching sessions). We also examine the efficacy of an abridged intervention (use of the Garmin Vivofit 2 only) in the waitlist control group. Methods: A pre‐post design was employed to examine the secondary aims of the ACTIVATE Trial (n = 80; mean age = 62 years). MVPA and sedentary behavior were measured using Actigraph and activPAL accelerometers after delivery of the primary intervention (T2), and again 12 weeks later (T3). Linear mixed models with random effects were used to examine within‐group changes in MVPA and sitting time variables. Results: After the 12‐week follow‐up period, women in the primary intervention group had maintained their higher levels of MVPA (change from T2 to T3 = 14 min/wk; 95% CI = −18 to 46; P  = .37). However, their sitting time increased slightly, by 7 min/d (95% CI = −20 to 34; P  = .58), but it did not return to its preintervention level. After receiving the Garmin Vivofit 2, the waitlist control group increased their MVPA by 33 min/wk (95% CI = 3‐64; P  = .03) and reduced their sitting time by 38 min/d (95% CI = −69 to −7; P  = .02) over the same 12‐week period. Conclusion: The secondary outcomes from the ACTIVATE Trial suggest that wearable technology may generate sustainable changes in MVPA and sitting time. Wearable technology alone may be sufficient to change behavior, at least in the short term. Abstract : Participants who receive the ACTIVATE Trial intervention successfully maintain an increased level of moderate to vigorous physical activity (MVPA) across the 12‐week follow‐up period, but the reduction in sedentary behavior is eroded. Receipt of the Garmin Vivofit 2 activity tracker alone is associated with a significant increase in MVPA and a reduction in sedentary behavior within the waitlist control arm.